Polyolefin composition and product

Through the blend of acrylic copolymer and polybutene elastomer, the problem of TPO resin being difficult to take into account both mechanical properties and transparency is solved, and high-performance and economical film or sheet preparation is achieved, suitable for new automotive interiors and Photovoltaic system.

CN119137206APending Publication Date: 2024-12-13EQUISTAR CHEMICALS LP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037987.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-03
Filing Date
2023-05-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing thermoplastic olefin composition (TPO) resins are difficult to balance mechanical properties and high transparency in automotive interiors and photovoltaic systems, and expensive additives are often required to improve transparency, affecting economics and processing performance.

Method used

Using a blend of acrylic copolymer composition and polybutene elastomer, by adjusting its composition ratio and polymerization method, a film or sheet with excellent softness, strength, processing performance and optical properties is prepared to meet the needs of new automobiles. Interior and photovoltaic system requirements.

Benefits of technology

It achieves mechanical properties comparable to traditional TPO resins, while improving transparency and processing properties, avoiding the need for expensive additives, and meeting the multiple performance requirements of new applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114508060000281
    Figure BDA0005114508060000281
  • Figure BDA0005114508060000291
    Figure BDA0005114508060000291
  • Figure BDA0005114508060000331
    Figure BDA0005114508060000331
Patent Text Reader

Abstract

Provided is a composition comprising a blend of a propylene-based copolymer composition and a polybutylene elastomer, and having both a balance of softness and strength and enhanced optical properties. Also provided is a film comprising the propylene-based copolymer composition and a polybutylene elastomer. The film may have a propylene-based copolymer composition and a polybutylene elastomer as separate layers in a multilayer structure, or may form a single layer from a blend of a propylene-based copolymer composition and a polybutylene elastomer. Methods of making the compositions and films are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is filed under the Patent Cooperation Treaty and claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 337,752, filed on May 3, 2022, which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to blends of propylene-based copolymer compositions and polybutylene elastomers. Films produced from such blends or films containing layers composed of propylene-based copolymer compositions and polybutylene elastomers exhibit an effective combination of softness, strength, processability and optical properties. Background Art

[0004] Thermoplastic olefin ("TPO") compositions typically include a blend of an olefin homopolymer (e.g., polypropylene) and a rubbery copolymer of two different alpha-olefins (e.g., ethylene-octene copolymer). The rubbery copolymer increases the impact strength or toughness of the TPO composition while also reducing the tensile modulus or stiffness of the TPO composition. Compared to such mechanical blends, the Catalloy® used by LyondellBasell TM The TPO resin produced by the process is an alloy of rubber and polypropylene, which is continuously produced in a polymerization reactor. These alloys allow the rubber to be better dispersed in the TPO resin, which directly affects the processing consistency and end-use performance.

[0005] Although TPO resins have long been used as automotive interior skins, some newer interior designs require interior skin materials to maintain a conventional appearance, but also have translucent properties that allow light to be projected through the skin. This technology can create a unique interior atmosphere during the day and at night, such as, but not limited to, allowing new electronic indicator locations and sizes. The operation of this technology can be enhanced by using interior skin materials with higher transparency.

[0006] In addition to the surface layer of the automotive interior, soft and transparent TPO resins are also beneficial in many other applications, including but not limited to the newly developed photovoltaic (PV) systems. Soft and transparent TPO resins can be used as sealing materials for PV cells and as transparent front sheets to protect the sealing film. In such PV systems, solar cells can be encapsulated in a soft and transparent sheet that allows light to pass through to the PV electronic components while allowing the sheet as a whole to be flexible.

[0007] These new automotive interior design and PV system applications have created a need for TPO compositions that combine a balance of mechanical properties comparable to existing TPO resins with improved clarity. A valuable approach would avoid expensive additives and performance compromises. Ideally, improved TPO compositions could be prepared using economical starting materials, common equipment, and familiar techniques. Summary of the invention

[0008] In general, the present invention relates to compositions and films and / or sheets containing propylene-based copolymer compositions and polybutylene elastomers, as well as methods for making such compositions, and films and / or sheets produced therefrom. In some film embodiments, the propylene-based copolymer composition and the polybutylene elastomer are blended to produce a monolayer film. In other film embodiments, a core layer of polybutylene elastomer is disposed between two outer layers of the propylene-based copolymer composition. In further embodiments, the compositions and films disclosed herein have a haze value less than or equal to 30%, and a tensile modulus (Young's modulus) in the range of 10 MPa to 350 MPa. The softness and strength of the combination of the propylene-based copolymer composition and the polybutylene elastomer are comparable to some existing TPO resins, and the optical properties are improved.

[0009] The propylene-based copolymer composition is a blend of at least two random copolymers of propylene and one or more α-olefins, such that units derived from different monomers and / or comonomers occur randomly along the polymer chain; wherein the α-olefin is selected from ethylene and C4-C8 monomers, selected from ethylene and C4-C6 monomers, or selected from ethylene and butene. This is in direct contrast to block copolymers or terpolymers, in which multiple common monomer units are aggregated together to form homopolymer segments along the polymer backbone.

[0010] In some embodiments, the monomer units of the random propylene-based copolymer composition are derived from ethylene, propylene and butene. In some embodiments, the melt flow rate (230°C / 2.16kg) of the propylene-based copolymer composition is in the range of 0.9 g / 10 min to 7.5 g / 10 min, and the density is 0.88 g / cm 3 Up to 0.92g / cm 3 In some embodiments, the polymerization process comprises the use of a spherical Ziegler-Natta catalyst, two or more (in some cases at least three) gas phase reactors operated in series, or a combination thereof. In various embodiments, the propylene-based copolymer composition may be characterized by any combination or all of the above-mentioned features and attributes.

[0011] In some embodiments, the polybutene elastomer is a copolymer obtained by polymerization of butene-1 and ethylene. In some embodiments, the polybutene elastomer has a melt flow rate (190°C / 2.16kg) in the range of 0.5 g / 10 min to 4 g / 10 min, a density of 0.870 g / cm 3 Up to 0.915g / cm 3 In some embodiments, the polybutene elastomer is polymerized in a process comprising a metallocene catalyst, a Ziegler-Natta catalyst, or a combination thereof. In various embodiments, the polybutene elastomer may be characterized by any combination or all of the above-described features and attributes.

[0012] The features and technical advantages of the present invention have been outlined quite extensively above so that the following detailed description of the invention may be better understood. Additional features and advantages of the present invention will be described below, which form the subject matter of the claims of the present invention. It will be appreciated by those skilled in the art that the disclosed concepts and specific embodiments may be easily used as a basis for modifying or designing other membrane structures and / or processes for achieving the same purposes of the present invention. It will also be appreciated by those skilled in the art that such equivalent constructions do not depart from the spirit and scope of the present invention as set forth in the appended claims. The novel features considered to be characteristic of the present invention, including its structure and method of manufacture, and further objects and advantages will be better understood from the following description. DETAILED DESCRIPTION

[0013] Illustrative embodiments of the subject matter claimed below will now be disclosed. For the sake of clarity, some features of some actual implementations may not be described in this specification. It should be understood that in the development of any such actual implementation, many implementation-specific decisions must be made to achieve the developer's specific goals, such as compliance with system-related and business-related constraints, which will vary from implementation to implementation. In addition, it should be understood that such development efforts, even if complex and time-consuming, are routine tasks for those of ordinary skill in the art who benefit from this disclosure.

[0014] The words and phrases used herein should be understood and interpreted as having a meaning consistent with the understanding of those words and phrases by those skilled in the relevant art. A special definition of a term or phrase, i.e., a definition that is different from the ordinary and customary meaning as understood by those skilled in the art, is a special definition of a term or phrase by those skilled in the art. To the extent that a term or phrase is intended to have a special meaning, i.e., a meaning that is different from the broadest meaning as understood by those skilled in the art, such special or clear definition will be expressly set forth in the specification in a definitional manner that provides a special or clear definition for the term or phrase.

[0015] For example, the following discussion includes a non-exhaustive list of definitions of several specific terms used in this disclosure (other terms may be defined or clarified in the manner defined elsewhere herein). These definitions are intended to clarify the meaning of the terms used herein. It is believed that the terms are used in a manner consistent with their ordinary meanings, but for clarity, the definitions are specified here.

[0016] definition

[0017] The term "about" means the stated value plus or minus the margin of measurement error, or plus or minus 10% if no measurement method is indicated.

[0018] As used herein, "compounding conditions" refers to the melt conditions induced by the temperature, pressure and shear conditions implemented in the extruder to provide intimate mixing of two or more polymers and optional additives to produce a substantially uniform polymer product. However, such temperature, pressure and shear conditions are limited to prevent chain scission and / or crosslinking of the blend components in the extruder, or to limit chain scission and / or crosslinking of the blend components in the extruder to produce an intimate blend of the mixed components, each component retaining its original properties.

[0019] As used herein, "film" is intended to include films (thickness ≤ 10 mils (0.25 mm)) or sheets (thickness ≥ 10 mils (0.25 mm)) as defined in "ASTM D883-Standard Terminology Relating to Plastics". In some embodiments, the term "film" as used herein is intended to include polymer films or sheets having a thickness ranging from greater than 0 to 100 mils (2.5 mm).

[0020] "Processability" as used herein refers to the use of the equipment and conditions described in the examples below in this specification to evaluate whether a polymer can successfully form a commercial quality cast film at a commercially acceptable rate. If a polymer composition can be processed into a film that can withstand the film performance test of this article, and if it is believed that such a polymer can continuously pass through the cast film equipment in a basically stable state manner under the conditions, then the polymer composition has good processability. If a polymer composition cannot be processed into a film that can withstand the film performance test of this article, or if it is believed that such a polymer cannot continuously pass through the cast film equipment in a basically stable state manner under the conditions, then the polymer composition does not have good processability.

[0021] Blended composition

[0022] Some new automotive interior designs and recently developed photovoltaic systems require higher transparency than many TPO resins currently used as surface layers for instrument panels and other interior surfaces. The combination of different polymers disclosed herein provides a beneficial balance of softness, strength, processability and optical properties to meet some of the requirements of these new automotive interior designs and PV systems.

[0023] It has been found that the blend of one or more propylene-based copolymer compositions and one or more polybutene elastomers provides various combinations of softness, intensity and transparency. In some embodiments, the amount of one or more propylene-based copolymer compositions present in the blended composition is in the range of 20 wt % to 80 wt %, 21 wt % to 70 wt %, 22 wt % to 60 wt %, 23 wt % to 50 wt %, 24 wt % to 40 wt % or 25 wt % to 35 wt %, wherein all weight percentages are based on the gross weight of one or more propylene-based copolymer compositions and one or more polybutene elastomers. Accordingly, the amount of one or more polybutene elastomers present in the blended composition is in the range of 20 wt % to 80 wt %, 30 wt % to 79 wt %, 40 wt % to 78 wt %, 50 wt % to 77 wt %, 60 wt % to 76 wt % or 65 wt % to 75 wt %, wherein all weight percentages are based on the gross weight of one or more propylene-based copolymer compositions and one or more polybutene elastomers.

[0024] In some embodiments, the blended composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers has a haze value of less than, or equal to, 23%, less than, or equal to, 20%, less than, or equal to, 17%, less than, or equal to, 14%, or less than, or equal to, 10%.

[0025] In some embodiments, the tensile modulus of a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is in the range of 10 MPa to 350 MPa, 15 MPa to 300 MPa, 20 MPa to 250 MPa, 25 MPa to 200 MPa, or 30 MPa to 175 MPa.

[0026] In some embodiments, one or more propylene-based copolymer compositions and one or more polybutylene elastomers are blended by adding the blending components to an extruder in the form of flakes and / or pellets and subjecting the physical mixture to compounding conditions sufficient to intimately mix the blending components to form a blended melt composition without substantially changing the original blending components. The blended melt composition can be extruded to form a cast film.

[0027] Propylene-based copolymer composition

[0028] The propylene-based copolymer composition comprises a random copolymer of propylene and one or more alpha-olefins, such that units derived from different monomers and / or comonomers occur randomly along the polymer chain. Exemplary propylene-based copolymer compositions and methods of producing such compositions are disclosed in U.S. Pat. No. 6,395,831, which is fully incorporated herein by reference in all jurisdictions that allow such incorporation. This is in contrast to block copolymers or terpolymers, in which multiple common monomer units are aggregated together to form homopolymer segments along the polymer backbone.

[0029] In some embodiments, the monomer units of the propylene-based copolymer composition are derived from ethylene, propylene, and C4-C8 monomers; derived from ethylene, propylene, and C4-C6 monomers; or derived from ethylene, propylene, and butene.

[0030] In some embodiments, the propylene-based copolymer composition comprises a propylene-based polyolefin having a melt flow rate of 2 g / 10 min to 15 g / 10 min, wherein the MFR value is measured according to ASTM D 1238 (230° C. / 2.16 kg). The propylene-based polyolefin may have a semi-crystalline propylene copolymer composition having: (A) 20 wt% to 80 wt% of one or more propylene-based components selected from: propylene / ethylene copolymers containing 1 wt% to 7 wt% ethylene; copolymers of propylene and one or more C4-C8 α-olefins containing 2 wt% to 10 wt% C4-C8 α-olefins; or terpolymers of propylene, ethylene and one or more C4-C8 α-olefins containing 0.5 wt% to 4.5 wt% ethylene and 2 wt% to 30 wt% propylene. 6 wt % of C4-C8 α-olefins, provided that the total content of ethylene and C4-C8 α-olefins is equal to or less than 6.5 wt %; and (B) 20 wt % to 80 wt % of one or more propylene-based components, the propylene-based components are selected from: copolymers of propylene and one or more C4-C8 α-olefins, which contain more than 10 wt % to 30 wt % of C4-C8 α-olefins, or terpolymers of propylene, ethylene and one or more C4-C8 α-olefins, which contain 1 wt % to 7 wt % of ethylene and 6 wt % to 15 wt % of C4-C8 α-olefins. Alternatively, the propylene-based polyolefin may have a semi-crystalline propylene copolymer composition having: (A) about 35 wt% of one or more propylene-based components selected from: a propylene / ethylene copolymer containing about 3.7 wt% ethylene; a copolymer of propylene with one or more C4-C8 alpha-olefins containing from 2 wt% to 10 wt% C4-C8 alpha-olefins; or a terpolymer of propylene with ethylene and one or more C4-C8 alpha-olefins containing from 0.5 wt% to 4.5 wt% ethylene. and 2 wt % to 6 wt % of C4-C8 α-olefins, provided that the total content of ethylene and C4-C8 α-olefins is equal to or less than 6.5 wt %; and (B) about 65 wt % of one or more propylene-based components, the propylene-based components being selected from: copolymers of propylene and one or more C4-C8 α-olefins containing from more than 10 wt % to 30 wt % of C4-C8 α-olefins; or terpolymers of propylene with ethylene and one or more C4-C8 α-olefins containing about 3.3 wt % of ethylene and about 10 wt % of C4 α-olefins.Alternatively, the propylene-based polyolefin may have a semi-crystalline propylene copolymer composition having: (A) about 35 wt% of a propylene-based component, which is a propylene / ethylene copolymer containing about 3.7 wt% of ethylene; and (B) about 65 wt% of a propylene-based component, which is a terpolymer of propylene with ethylene and a C4 alpha-olefin containing about 3.3 wt% of ethylene and about 10 wt% of a C4 alpha-olefin. In some embodiments, the density of the propylene-based copolymer composition is 0.88 g / cm. 3 Up to 0.92g / cm 3 , 0.88g / cm 3 Up to 0.92g / cm 3 , 0.89g / cm 3 Up to 0.91g / cm 3 , 0.895g / cm 3 Up to 0.905g / cm 3 , or 0.898g / cm 3 To 0.902g / cm 3 within the range.

[0031] In some embodiments, the propylene-based copolymer composition has a tensile modulus in a range from 100 MPa to 1000 MPa, from 150 MPa to 950 MPa, from 250 MPa to 900 MPa, from 350 MPa to 850 MPa, or from 450 MPa to 800 MPa.

[0032] In some embodiments, the propylene-based copolymer composition is produced in a polymerization process such as, but not limited to, Catalloy TM Process (performed by LyondellBasell). In some embodiments, the polymerization process comprises the use of a spherical Ziegler-Natta catalyst, two or more (in some cases at least three) gas phase reactors operated in series, or a combination thereof.

[0033] In some embodiments, the propylene-based copolymer composition or a film formed from the propylene-based copolymer composition has a gloss greater than, or equal to, 50 GU, greater than, or equal to, 60 GU, greater than, or equal to, 70 GU, greater than, or equal to, 80 GU, or greater than, or equal to, 90 GU.

[0034] In some embodiments, the propylene-based copolymer composition or a film formed from the propylene-based copolymer composition has a thickness of less than or equal to 20 mils (0.51 mm) and a haze of less than or equal to 45%, less than or equal to 35%, less than or equal to 25%, or less than or equal to 15%.

[0035] In some embodiments, the propylene-based copolymer composition or a film formed from the propylene-based copolymer composition has a tensile stress at break in a range from 15 MPa to 75 MPa, 20 MPa to 55 MPa, 25 MPa to 45 MPa, or 30 MPa to 35 MPa.

[0036] In some embodiments, the propylene-based copolymer composition or a film formed from the propylene-based copolymer composition has an elongation at break in a range of 50% to 500%, 100% to 400%, 150% to 300%, or 200% to 250%.

[0037] In various embodiments, the propylene-based copolymer composition is characterized by any combination or all of the above-described attributes.

[0038] Polybutylene elastomer

[0039] In some embodiments, the polybutene elastomer is obtained by polymerization of butene-1 and ethylene.Such polybutene elastomers and methods of producing such compositions are disclosed in PCT Publication No. WO 2009 / 000637, which is fully incorporated herein by reference for all jurisdictions where such incorporation is permitted.

[0040] In some embodiments, the polybutylene elastomer has a melt flow rate (190°C / 2.16 kg) in the range of 0.5 g / 10 min to 4 g / 10 min, a density in the range of 0.870 g / cm 3 Up to 0.915g / cm 3 The tensile modulus is in the range of 1MPa to 100MPa, 2MPa to 90MPa, 3MPa to 80MPa, 4MPa to 70MPa, 5MPa to 60MPa, or 10MPa to 50MPa, and the tensile elongation at break is greater than or equal to 300%, 400%, 500% or 600%, or any combination thereof.

[0041] In some embodiments, the polybutylene elastomer has an ethylene-derived unit content in the range of 15.10 mol % to 18.00 mol %, 15.50 mol % to 17 mol %, or 15.50 mol % to 16.50 mol % and has the following properties:

[0042] a) Molecular weight distribution M w / M n Less than 3;

[0043] b) a Shore A hardness (measured according to ISO 868) of less than 65, or less than 60;

[0044] c) At 100% deformation, the tensile set is less than 30% or less than 20% (ISO 2285);

[0045] d) no detectable melting point by DSC as measured by the following method; and

[0046] e) a melting enthalpy in the range of 4 J / g to 15 J / g, or 5 J / g to 10 J / g, measured after aging for 10 days at room temperature according to the method described below.

[0047] In some embodiments, in addition to exhibiting good clarity values, the polybutylene elastomers have a good balance between hardness and elastic behavior, which is better described by tensile set.

[0048] In some embodiments, the polybutylene elastomer does not exhibit a melting point after being melted according to conventional DSC procedures; however, it is crystallizable, ie, the copolymer exhibits a melting point and melting enthalpy about 10 days after the polybutylene elastomer is melted.

[0049] In some embodiments, the polybutylene elastomer has a tensile stress at break, measured according to ISO 527, in a range of 3 MPa to 20 MPa, or 4 MPa to 13 MPa.

[0050] In some embodiments, the polybutylene elastomer has an elongation at break measured according to ISO 527 in the range of 550% to 800%, or 600% to 750%.

[0051] In some embodiments, the polybutylene elastomer has a high molecular weight, as indicated by an intrinsic viscosity ("IV") greater than 1, greater than 1.5, or greater than 2. In some embodiments, the IV is less than or equal to 3.

[0052] In some embodiments, the polybutylene elastomer or a film formed from the polybutylene elastomer has a tensile modulus in a range from 6 MPa to 30 MPa, from 8 MPa to 25 MPa, from 10 MPa to 20 MPa, or from 12 MPa to 15 MPa.

[0053] In some embodiments, the polybutylene elastomer or a film formed from the polybutylene elastomer has a gloss of less than or equal to 25 GU, less than or equal to 20 GU, less than or equal to 15 GU, less than or equal to 12 GU, or less than or equal to 10 GU.

[0054] In some embodiments, the polybutylene elastomer or a film formed from the polybutylene elastomer has a haze greater than or equal to 60%, greater than or equal to 65%, greater than or equal to 70%, greater than or equal to 75%, greater than or equal to 80%, or greater than or equal to 85%.

[0055] In some embodiments, the polybutylene elastomer or a film formed therefrom has a tensile stress at break in a range of 6 MPa to 30 MPa, 7 MPa to 25 MPa, 8 MPa to 20 MPa, 25 MPa to 9 MPa, or 10 MPa to 12 MPa.

[0056] In some embodiments, the polybutylene elastomer or a film formed from the polybutylene elastomer has an elongation at break of greater than or equal to 300%, greater than or equal to 400%, greater than or equal to 500%, greater than or equal to 600%, greater than or equal to 700%, or greater than or equal to 800%.

[0057] In some embodiments, the polybutylene elastomer or a film formed from the polybutylene elastomer has a puncture resistance in a range of 4.0N to 5.0N, 3.5N to 5.5N, 3.0N to 6.0N, 2.5N to 6.5N, or 2.0N to 7.0N.

[0058] In some embodiments, the polybutylene elastomer or a film formed from the polybutylene elastomer has a Shore A hardness (after 15 seconds) in a range of 50-70, 52-68, 53-67, 54-66, or 55-65.

[0059] In some embodiments, the polybutylene elastomer or film formed from the polybutylene elastomer has a maximum extension in transverse tear resistance in a range of 80 mm to 130 mm, 85 mm to 125 mm, 90 mm to 120 mm, 95 mm to 115 mm, or 100 mm to 110 mm.

[0060] In various embodiments, the polybutylene elastomer may be characterized by any combination or all of the above-described characteristics and properties.

[0061] membrane

[0062] The films disclosed herein comprise one or more propylene-based copolymer compositions as described above and one or more polybutylene elastomers as described above.

[0063] In some embodiments, the tensile modulus of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is in the range of 10 MPa to 350 MPa, 15 MPa to 300 MPa, 20 MPa to 250 MPa, 25 MPa to 200 MPa, or 30 MPa to 175 MPa.

[0064] In some embodiments, the gloss of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is in the range of 15 GU or greater, 25 GU or greater, 35 GU or greater, 45 GU or greater, 55 GU or greater, or 65 GU or greater.

[0065] In some embodiments, the haze of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is less than, or equal to, 65%, less than, or equal to, 55%, less than, or equal to, 45%, less than, or equal to, 35%, less than, or equal to, 25%, or less than, or equal to, 15%.

[0066] In some embodiments, the transmittance of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is greater than, or equal to, 90%, greater than, or equal to, 92%, or greater than, or equal to, 95% when the film thickness is at least 0.5 mm.

[0067] In some embodiments, the tensile stress at break of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is in the range of 1 MPa to 100 MPa, 2 MPa to 80 MPa, 20 MPa to 60 MPa, 25 MPa to 45 MPa, or 15 MPa to 30 MPa.

[0068] In some embodiments, the elongation at break of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is greater than, or equal to, 300%, greater than, or equal to, 400%, greater than, or equal to, 500%, greater than, or equal to, 600%, greater than, or equal to, 700%, or greater than, or equal to, 800%.

[0069] In some embodiments, the 1% secant modulus of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is from 30 MPa to 360 MPa, from 40 MPa to 250 MPa, from 50 MPa to 200 MPa, or from 60 MPa to 150 MPa.

[0070] In some embodiments, the puncture resistance of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is greater than, or equal to, 75 N, greater than, or equal to, 80 N, greater than, or equal to, 85 N, greater than, or equal to, 90 N, or greater than, or equal to, 100 N.

[0071] In some embodiments, the Shore A Hardness (after 15 seconds) of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is in the range of 50 to 90, 55 to 85, 60 to 80, or 65 to 75.

[0072] In some embodiments, the machine direction tear resistance of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is greater than, or equal to, 25 N, greater than, or equal to, 35 N, greater than, or equal to, 45 N, greater than, or equal to, 55 N, greater than, or equal to, 65 N, or greater than, or equal to, 75 N.

[0073] In some embodiments, the normalized machine direction tear resistance of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is greater than, or equal to, 50 N / mm, greater than, or equal to, 70 N / mm, greater than, or equal to, 90 N / mm, greater than, or equal to, 110 N / mm, greater than, or equal to, 130 N / mm, or greater than, or equal to, 150 N / mm.

[0074] In some embodiments, the maximum extension of machine direction tear resistance of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is greater than, or equal to, 50 mm, greater than, or equal to, 60 mm, greater than, or equal to, 70 mm, greater than, or equal to, 80 mm, greater than, or equal to, 90 mm, or greater than, or equal to, 100 mm.

[0075] In some embodiments, the transverse tear resistance of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is greater than, or equal to, 25 N, greater than, or equal to, 35 N, greater than, or equal to, 45 N, greater than, or equal to, 55 N, greater than, or equal to, 65 N, or greater than, or equal to, 75 N.

[0076] In some embodiments, the normalized transverse tear resistance of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is greater than, or equal to, 50 N / mm, greater than, or equal to, 70 N / mm, greater than, or equal to, 90 N / mm, greater than, or equal to, 110 N / mm, greater than, or equal to, 130 N / mm, or greater than, or equal to, 150 N / mm.

[0077] In some embodiments, the maximum extension in transverse tear of a film comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers is greater than, or equal to, 50 mm, greater than, or equal to, 60 mm, greater than, or equal to, 70 mm, greater than, or equal to, 80 mm, greater than, or equal to, 90 mm, or greater than, or equal to, 100 mm.

[0078] In various embodiments, films comprising the blend compositions, as disclosed herein, are characterized by any combination or all of the above-described attributes.

[0079] In some embodiments, the film comprises one or more propylene-based copolymer compositions and one or more polybutylene elastomers, and the film has a thickness ranging from 5 mils (127 μm) to 25 mils (635 μm), or from 10 mils (254 μm) to 20 mils (508 μm).

[0080] In some embodiments, the film comprises one or more propylene-based copolymer compositions and one or more polybutylene elastomers, the film comprises two outer layers and a core layer, the outer layer comprises the propylene-based copolymer composition, the core layer comprises the polybutylene elastomer, wherein the core layer is disposed between the two outer layers. In some embodiments, the thickness of the core layer is in the range of 50% to 85%, 55% to 83%, 60% to 81%, 65% to 79%, or 70% to 77%, wherein the percentage is based on the total thickness of the core layer and the two outer layers in the film. In addition, in some other embodiments, the thickness of the film is in the range of 5 mils (127 μm) to 25 mils (635 μm), or 10 mils (254 μm) to 20 mils (508 μm), while the core layer thickness is in the range of 50% to 85%, 55% to 83%, 60% to 81%, 65% to 79%, or 70% to 77% of the film thickness.

[0081] In some embodiments, in the cast film coextrusion process, at least three polymer layers are coextruded to produce layer configuration A / B / A, wherein A comprises a propylene-based copolymer composition, and B comprises a polybutylene elastomer as a core layer. In this type of multilayer coextrusion cast film method, the polymer of each layer is heated in a separate extruder. When the molten polymer arrives at the barrel end of each extruder, the polymer is coextruded to adopt its final shape by a multilayer flat die system. After leaving the die head, the multilayer melt enters a cooling unit, where its temperature is reduced with a water-cooled chill roll to solidify the film.

[0082] In some embodiments, one or both outer layers comprising one or more propylene-based copolymer compositions further comprise one or more polybutylene elastomers. In some embodiments, the core layer comprising one or more polybutylene elastomers further comprises one or more propylene-based copolymer compositions. In some embodiments, the core layer and one or both outer layers comprise one or more propylene-based copolymer compositions and one or more polybutylene elastomers.

[0083] In some embodiments, the film comprises one or more propylene-based copolymer compositions and one or more polybutylene elastomers, the propylene-based copolymer composition and the polybutylene elastomer are blended under melt conditions to form a blended composition, and the film is formed from the blended composition.

[0084] In some embodiments, in a cast film extrusion process, a blend of one or more propylene-based copolymer compositions and one or more polybutylene elastomers is melted in one or more extruders and extruded or coextruded to form a monolayer film comprising the blend of one or more propylene-based copolymer compositions and one or more polybutylene elastomers.

[0085] In some embodiments, three extruders are fed into a five-layer cast film apparatus to produce a three-layer film of configuration A-3 / B-2 / B-1 / B-2 / A-3 (i.e., extruder 1 feeds the core layer, extruder 2 feeds the second layer adjacent to the core layer, and extruder 3 feeds the outer layer, controlled by the die splitter), wherein A is one or more propylene-based copolymer compositions, B is one or more polybutene elastomers, and when the layers of the polybutene melt are co-extruded, no interface between the B layers is retained.

[0086] In some embodiments, three extruders are fed into a five-layer cast film apparatus to produce a monolayer film of AB-3 / AB-2 / AB-1 / AB-2 / AB-3 configuration (i.e., extruder 1 feeds the core layer, extruder 2 feeds the second layer adjacent to the core layer, and extruder 3 feeds the outer layer, as controlled by the die split flow), wherein AB is a blend of one or more propylene-based copolymer compositions and one or more polybutylene elastomers, and when the layers of the AB blend melt are co-extruded, no interface between the AB layers is retained.

[0087] The general process of forming a monolayer or trilayer structure using a cast film device suitable for making five or more layers can be controlled by feeding a common polymer to one or more adjacent layers. The monolayer or multilayer structure can be in the form of a film or sheet, which can be further thermoformed or oriented, and can be produced using conventional methods and extrusion equipment known to those skilled in the art, wherein the polymer melt layers are combined by introducing multiple polymer melt streams into a combined block / manifold or die, which then guides the melt streams to flow together (while still in the block / manifold or die), and then leaves the die together as a single flowing stream. Alternatively, multiple polymer melt streams can be introduced into the die and then merged immediately after leaving the die.

[0088] Certain embodiments

[0089] In some embodiments, the film consists essentially of a blend of:

[0090] (A) one or more propylene-based copolymer compositions present in the blend composition in an amount ranging from about 20 wt% to 80 wt%, 21 wt% to 70 wt%, 22 wt% to 60 wt%, 23 wt% to 50 wt%, 24 wt% to 40 wt%, 55 wt% to 80 wt%, or 25 wt% to 35 wt%, wherein all weight percentages are based on the combined weight of the one or more propylene-based copolymer compositions and the one or more polybutylene elastomers, and each propylene-based copolymer composition is characterized by one or more of the following:

[0091] (1) is a blend of random copolymers of propylene and one or more α-olefins, such that units derived from different monomers and / or comonomers appear randomly along the polymer chain; wherein the α-olefin is selected from ethylene and C4-C8 monomers, selected from ethylene and C4-C6 monomers, or selected from ethylene and butene; and / or

[0092] (2) is a semi-crystalline propylene copolymer composition having: (A) 20 wt% to 80 wt% of one or more propylene-based components selected from: propylene / ethylene copolymers containing 1 wt% to 7 wt% ethylene; copolymers of propylene and one or more C4-C8 α-olefins containing 2 wt% to 10 wt% of C4-C8 α-olefins; or terpolymers of propylene, ethylene and one or more C4-C8 α-olefins containing 0.5 wt% to 4.5 wt% of ethylene and 2 wt% to 6 wt% of C4-C8 α-olefins. 8 α-olefins, provided that the total content of ethylene and C4-C8 α-olefins is equal to or less than 6.5 wt%; and (B) 20 wt% to 80 wt% of one or more propylene-based components selected from: copolymers of propylene and one or more C4-C8 α-olefins, which contain more than 10 wt% to 30 wt% of C4-C8 α-olefins, or terpolymers of propylene with ethylene and one or more C4-C8 α-olefins, which contain 1 wt% to 7 wt% ethylene and 6 wt% to 15 wt% of C4-C8 α-olefins; and / or

[0093] (3) a melt flow rate between 2 g / 10 min and 15 g / 10 min; and / or

[0094] (4) Density is 0.88g / cm 3 Up to 0.92g / cm 3 , 0.88g / cm3 to 0.92g / cm 3 , 0.89g / cm 3 Up to 0.91g / cm 3 , 0.895g / cm 3 Up to 0.905g / cm 3 , or 0.898g / cm 3 To 0.902g / cm 3 to the extent that: and / or

[0095] (5) a tensile modulus in the range of 100 MPa to 1000 MPa, 150 MPa to 950 MPa, 250 MPa to 900 MPa, 350 MPa to 850 MPa, or 450 MPa to 800 MPa; and / or

[0096] (6) Glossiness greater than or equal to 50 GU, greater than or equal to 60 GU, greater than or equal to 70 GU, greater than or equal to 80 GU or greater than or equal to 90 GU; and / or

[0097] (7) haze less than or equal to 45%, less than or equal to 35%, less than or equal to 25%, or less than or equal to 15%; and / or

[0098] (8) a tensile stress at break in the range of 15 MPa to 75 MPa, 20 MPa to 55 MPa, 25 MPa to 45 MPa, or 30 MPa to 35 MPa;

[0099] (9) an elongation at break in the range of 50% to 500%, 100% to 400%, 150% to 300%, or 200% to 250%; and / or

[0100] (10) a 1% secant modulus of 5 MPa to 30 MPa, 6 MPa to 25 MPa, 8 MPa to 20 MPa, or 10 MPa to 15 MPa; and / or

[0101] (11) In some embodiments, the propylene-based copolymer composition or a film formed from the propylene-based copolymer composition has a 2% secant modulus of 200 MPa to 650 MPa, 250 MPa to 600 MPa, 300 MPa to 550 MPa, or 350 MPa to 500 MPa; and

[0102] (B) one or more polybutylene elastomers present in the blend composition in an amount ranging from about 20 wt% to 80 wt%, 30 wt% to 79 wt%, 40 wt% to 78 wt%, 50 wt% to 77 wt%, 60 wt% to 76 wt%, 40 wt% to 60 wt%, 20 wt% to 50 wt%, or 65 wt% to 75 wt%, wherein all weight percentages are based on the combined weight of the one or more propylene-based copolymer compositions and the one or more polybutylene elastomers, and each polybutylene elastomer is characterized by one or more of the following:

[0103] (1) is a copolymer obtained by polymerization of butene-1 and ethylene;

[0104] (2) Melt flow rate (190°C / 2.16kg) is in the range of 0.5 g / 10 min to 4 g / 10 min, and density is 0.870 g / cm 3 Up to 0.915g / cm 3 , a tensile modulus in the range of 1 MPa to 100 MPa, 2 MPa to 90 MPa, 3 MPa to 80 MPa, 4 MPa to 70 MPa, 5 MPa to 60 MPa, or 10 MPa to 50 MPa, and a tensile elongation at break greater than or equal to 300%, 400%, 500% or 600%, or any combination thereof; and / or

[0105] (3) an ethylene-derived unit content in the range of 15.10 mol % to 18.00 mol %, 15.50 mol % to 17 mol %, or 15.50 mol % to 16.50 mol %; and / or

[0106] (4) Molecular weight distribution M w / M n Less than 3; and / or

[0107] (5) a Shore A hardness (measured according to ISO 868) of less than 65, or less than 60; and / or

[0108] (6) A tensile set (ISO 2285) of less than 30% or less than 20% at 100% deformation; and / or

[0109] (7) does not exhibit a melting point after melting according to a conventional DSC procedure; however, it is crystallizable, i.e., the copolymer exhibits a melting point and melting enthalpy about 10 days after it has melted; and / or

[0110] (8) a melting enthalpy in the range of 4 J / g to 15 J / g, or 5 J / g to 10 J / g, measured after aging for 10 days at room temperature; and / or

[0111] (9) In addition to showing good clarity values, have a good balance between hardness and elasticity behavior, which balance is better described by tensile set; and / or

[0112] (10) a tensile stress at break in the range of 3 MPa to 20 MPa, or 4 MPa to 13 MPa, measured according to ISO 527; and / or

[0113] (11) an elongation at break in the range of 550% to 800%, or 600% to 750%, measured according to ISO 527; and / or

[0114] (12) having a high molecular weight, as indicated by an intrinsic viscosity ("IV") greater than 1, greater than 1.5, or greater than 2. In some embodiments, the IV is less than or equal to 3; and / or

[0115] (13) polymerized in a process comprising a metallocene catalyst, a Ziegler-Natta catalyst, or a combination thereof; and / or

[0116] (14) a tensile modulus in the range of 6 MPa to 30 MPa, 8 MPa to 25 MPa, 10 MPa to 20 MPa, or 12 MPa to 15 MPa; and / or

[0117] (15) gloss less than or equal to 25 GU, less than or equal to 20 GU, less than or equal to 15 GU, less than or equal to 12 GU, or less than or equal to 10 GU; and / or

[0118] (16) a haze of 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, or 85% or more; and / or

[0119] (17) a tensile stress at break in the range of 6 MPa to 30 MPa, 7 MPa to 25 MPa, 8 MPa to 20 MPa, 25 MPa to 9 MPa, or 10 MPa to 12 MPa; and / or

[0120] (18) an elongation at break of 300% or more, 400% or more, 500% or more, 600% or more, 700% or more, or 800% or more; and / or

[0121] (19) a puncture resistance in the range of 4.0 N to 5.0 N, 3.5 N to 5.5 N, 3.0 N to 6.0 N, 2.5 N to 6.5 N, or 2.0 N to 7.0 N; and / or

[0122] (20) a Shore A hardness (after 15 seconds) in the range of 50 to 70, 52 to 68, 53 to 67, 54 to 66, or 55 to 65; and / or

[0123] (21) a machine direction tear resistance in the range of 20N to 36N, 22N to 34N, 23N to 32N, 24N to 30N, or 25N to 28N; and / or

[0124] (22) a normalized machine direction tear resistance in the range of 40 N / mm to 72 N / mm, 44 N / mm to 68 N / mm, 46 N / mm to 64 N / mm, 48 N / mm to 60 N / mm, or 50 N / mm to 56 N / mm; and / or

[0125] (23) a machine direction tear resistance maximum extension in the range of 80 mm to 130 mm, 85 mm to 125 mm, 90 mm to 120 mm, 95 mm to 115 mm, or 100 mm to 110 mm; and / or

[0126] (24) a transverse tear resistance in the range of 20N to 36N, 22N to 34N, 23N to 32N, 24N to 30N, or 25N to 28N; and / or

[0127] (25) a normalized transverse tear resistance in the range of 40 N / mm to 72 N / mm, 44 N / mm to 68 N / mm, 46 N / mm to 64 N / mm, 48 N / mm to 60 N / mm, or 50 N / mm to 56 N / mm; and / or

[0128] (26) a maximum transverse tear extension in the range of 80 mm to 130 mm, 85 mm to 125 mm, 90 mm to 120 mm, 95 mm to 115 mm, or 100 mm to 110 mm; and

[0129] The film is characterized by one or more of the following:

[0130] (A) a haze value of less than or equal to 23%, less than or equal to 20%, less than or equal to 17%, less than or equal to 14%, or less than or equal to 10%; and / or

[0131] (B) a tensile modulus in the range of 10 MPa to 350 MPa, 15 MPa to 300 MPa, 20 MPa to 250 MPa, 25 MPa to 200 MPa, or 30 MPa to 175 MPa; and / or

[0132] (C) comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers having a tensile modulus in the range of 10 MPa to 350 MPa, 15 MPa to 300 MPa, 20 MPa to 250 MPa, 25 MPa to 200 MPa, or 30 MPa to 175 MPa; and / or

[0133] (D) comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers, having a gloss of greater than or equal to 15 GU, greater than or equal to 25 GU, greater than or equal to 35 GU, greater than or equal to 45 GU, greater than or equal to 55 GU, or greater than or equal to 65 GU; and / or

[0134] (E) comprises a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers, and having a haze of less than or equal to 65%, less than or equal to 55%, less than or equal to 45%, less than or equal to 35%, less than or equal to 25%, or less than or equal to 15%; and / or

[0135] (F) comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers having a tensile stress at break in the range of 1 MPa to 100 MPa, 2 MPa to 80 MPa, 20 MPa to 60 MPa, 25 MPa to 45 MPa, or 15 MPa to 30 MPa; and / or

[0136] (G) comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers, having an elongation at break of greater than or equal to 300%, greater than or equal to 400%, greater than or equal to 500%, greater than or equal to 600%, greater than or equal to 700%, or greater than or equal to 800%; and / or

[0137] (H) a 1% secant modulus of 30 MPa to 360 MPa, 40 MPa to 250 MPa, 50 MPa to 200 MPa, or 60 MPa to 150 MPa; and / or

[0138] (I) a 2% secant modulus of 25 MPa to 260 MPa, 30 MPa to 230 MPa, 35 MPa to 200 MPa, or 40 MPa to 150 MPa; and / or

[0139] (J) a puncture resistance of greater than or equal to 75 N, greater than or equal to 80 N, greater than or equal to 85 N, greater than or equal to 90 N, or greater than or equal to 100 N; and / or

[0140] (K) a Shore A hardness (after 15 seconds) in the range of 50 to 90, 55 to 85, 60 to 80, or 65 to 75; and / or

[0141] (L) a machine direction tear resistance of greater than or equal to 25 N, greater than or equal to 35 N, greater than or equal to 45 N, greater than or equal to 55 N, greater than or equal to 65 N, or greater than or equal to 75 N; and / or

[0142] (M) a normalized machine direction tear resistance of greater than or equal to 50 N / mm, greater than or equal to 70 N / mm, greater than or equal to 90 N / mm, greater than or equal to 110 N / mm, greater than or equal to 130 N / mm, or greater than or equal to 150 N / mm; and / or

[0143] (N) a maximum machine direction tear extension of 50 mm or more, 60 mm or more, 70 mm or more, 80 mm or more, 90 mm or more, or 100 mm or more; and / or

[0144] (O) a transverse tear resistance of greater than or equal to 25 N, greater than or equal to 35 N, greater than or equal to 45 N, greater than or equal to 55 N, greater than or equal to 65 N, or greater than or equal to 75 N; and / or

[0145] (P) a normalized transverse tear resistance of greater than or equal to 50 N / mm, greater than or equal to 70 N / mm, greater than or equal to 90 N / mm, greater than or equal to 110 N / mm, greater than or equal to 130 N / mm, or greater than or equal to 150 N / mm; and / or

[0146] (Q) Transverse tear resistance with a maximum extension of greater than or equal to 50 mm, greater than or equal to 60 mm, greater than or equal to 70 mm, greater than or equal to 80 mm, greater than or equal to 90 mm, or greater than or equal to 100 mm.

[0147] In some embodiments, one or more propylene-based copolymer compositions and one or more polybutylene elastomers are blended by adding the blending components to an extruder in the form of flakes and / or pellets and subjecting the physical mixture to compounding conditions sufficient to fully mix the blending components to form a blended melt composition without substantially changing the original blending components. The blended melt composition can be extruded to form a cast film.

[0148] In some embodiments, the membrane comprises:

[0149] (A) two outer layers having one or more propylene-based copolymer compositions, and each propylene-based copolymer composition is characterized by one or more of the following:

[0150] (1) is a blend of random copolymers of propylene and one or more α-olefins, such that units derived from different monomers and / or comonomers appear randomly along the polymer chain; wherein the α-olefin is selected from ethylene and C4-C8 monomers, selected from ethylene and C4-C6 monomers, or selected from ethylene and butene; and / or

[0151] (2) is a semi-crystalline propylene copolymer composition having: (A) 20 wt% to 80 wt% of one or more propylene-based components selected from: propylene / ethylene copolymers containing 1 wt% to 7 wt% ethylene; copolymers of propylene and one or more C4-C8 α-olefins containing 2 wt% to 10 wt% C4-C8 α-olefins; or terpolymers of propylene, ethylene and one or more C4-C8 α-olefins containing 0.5 wt% to 4.5 wt% ethylene and 2 wt% to 6 wt% C4-C8 α-olefins. -C8 α-olefins, provided that the total content of ethylene and C4-C8 α-olefins is equal to or less than 6.5 wt%; and (B) 20 wt% to 80 wt% of one or more propylene-based components selected from: copolymers of propylene with one or more C4-C8 α-olefins, which contain more than 10 wt% to 30 wt% of C4-C8 α-olefins; or terpolymers of propylene with ethylene and one or more C4-C8 α-olefins, which contain 1 wt% to 7 wt% of ethylene and 6 wt% to 15 wt% of C4-C8 α-olefins;

[0152] (3) a melt flow rate between 2 g / 10 min and 15 g / 10 min; and / or

[0153] (4) Density is 0.88g / cm 3 Up to 0.92g / cm 3 , 0.88g / cm3 to 0.92g / cm 3 , 0.89g / cm 3 Up to 0.91g / cm 3 , 0.895g / cm3 Up to 0.905g / cm 3 , or 0.898g / cm 3 To 0.902g / cm 3 to the extent that: and / or

[0154] (5) a tensile modulus in the range of 100 MPa to 1000 MPa, 150 MPa to 950 MPa, 250 MPa to 900 MPa, 350 MPa to 850 MPa, or 450 MPa to 800 MPa; and / or

[0155] (6) Gloss greater than or equal to 50 GU, greater than or equal to 60 GU, greater than or equal to 70 GU, greater than or equal to 80 GU, or greater than or equal to 90 GU; and / or

[0156] (7) haze less than or equal to 45%, less than or equal to 35%, less than or equal to 25%, or less than or equal to 15%; and / or

[0157] (8) a tensile stress at break in the range of 15 MPa to 75 MPa, 20 MPa to 55 MPa, 25 MPa to 45 MPa, or 30 MPa to 35 MPa;

[0158] (9) an elongation at break in the range of 50% to 500%, 100% to 400%, 150% to 300%, or 200% to 250%; and / or

[0159] (10) a 1% secant modulus of 5 MPa to 30 MPa, 6 MPa to 25 MPa, 8 MPa to 20 MPa, or 10 MPa to 15 MPa; and / or

[0160] (11) In some embodiments, the propylene-based copolymer composition or a film formed from the propylene-based copolymer composition has a 2% secant modulus of 200 MPa to 650 MPa, 250 MPa to 600 MPa, 300 MPa to 550 MPa, or 350 MPa to 500 MPa; and

[0161] (B) a core layer consisting essentially of one or more polybutylene elastomers, each polybutylene elastomer being characterized by one or more of the following:

[0162] (1) a copolymer obtained by polymerization of butene-1 and ethylene; and / or

[0163] (2) Melt flow rate (190°C / 2.16kg) is in the range of 0.5 g / 10 min to 4 g / 10 min, and density is 0.870 g / cm 3 Up to 0.915g / cm 3The tensile modulus is in the range of 1 MPa to 100 MPa, 2 MPa to 90 MPa, 3 MPa to 80 MPa, 4 MPa to 70 MPa, 5 MPa to 60 MPa, or 10 MPa to 50 MPa, and the tensile elongation at break is greater than or equal to 300%, or any combination thereof; and / or

[0164] (3) an ethylene-derived unit content in the range of 15.10 mol % to 18.00 mol %, 15.50 mol % to 17 mol %, or 15.50 mol % to 16.50 mol %; and / or

[0165] (4) Molecular weight distribution M w / M n Less than 3; and / or

[0166] (5) a Shore A hardness (measured according to ISO 868) of less than 65, or less than 60; and / or

[0167] (6) A tensile set (ISO 2285) of less than 30% or less than 20% at 100% deformation; and / or

[0168] (7) does not exhibit a melting point after melting according to a conventional DSC procedure; however, it is crystallizable, i.e., the copolymer exhibits a melting point and melting enthalpy about 10 days after it has melted; and / or

[0169] (8) a melting enthalpy in the range of 4 J / g to 15 J / g, or 5 J / g to 10 J / g, measured after aging for 10 days at room temperature; and / or

[0170] (9) In addition to showing good clarity values, have a good balance between hardness and elasticity behavior, which balance is better described by tensile set; and / or

[0171] (10) a tensile stress at break in the range of 3 MPa to 20 MPa, or 4 MPa to 13 MPa, measured according to ISO 527; and / or

[0172] (11) an elongation at break in the range of 550% to 800%, or 600% to 750%, measured according to ISO 527; and / or

[0173] (12) having a high molecular weight, as indicated by an intrinsic viscosity ("IV") greater than 1, greater than 1.5, or greater than 2. In some embodiments, the IV is less than or equal to 3; and / or

[0174] (13) polymerized in a process comprising a metallocene catalyst, a Ziegler-Natta catalyst, or a combination thereof; and / or

[0175] (14) a tensile modulus in the range of 6 MPa to 30 MPa, 8 MPa to 25 MPa, 10 MPa to 20 MPa, or 12 MPa to 15 MPa; and / or

[0176] (15) gloss less than or equal to 25 GU, less than or equal to 20 GU, less than or equal to 15 GU, less than or equal to 12 GU, or less than or equal to 10 GU; and / or

[0177] (16) a haze of 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, or 85% or more; and / or

[0178] (17) a tensile stress at break in the range of 6 MPa to 30 MPa, 7 MPa to 25 MPa, 8 MPa to 20 MPa, 25 MPa to 9 MPa, or 10 MPa to 12 MPa; and / or

[0179] (18) an elongation at break of 300% or more, 400% or more, 500% or more, 600% or more, 700% or more, or 800% or more; and / or

[0180] (19) a puncture resistance in the range of 4.0 N to 5.0 N, 3.5 N to 5.5 N, 3.0 N to 6.0 N, 2.5 N to 6.5 N, or 2.0 N to 7.0 N; and / or

[0181] (20) a Shore A hardness (after 15 seconds) in the range of 50 to 70, 52 to 68, 53 to 67, 54 to 66, or 55 to 65; and / or

[0182] (21) a machine direction tear resistance in the range of 20N to 36N, 22N to 34N, 23N to 32N, 24N to 30N, or 25N to 28N; and / or

[0183] (22) a normalized machine direction tear resistance in the range of 40 N / mm to 72 N / mm, 44 N / mm to 68 N / mm, 46 N / mm to 64 N / mm, 48 N / mm to 60 N / mm, or 50 N / mm to 56 N / mm; and / or

[0184] (23) a machine direction tear resistance maximum extension in the range of 80 mm to 130 mm, 85 mm to 125 mm, 90 mm to 120 mm, 95 mm to 115 mm, or 100 mm to 110 mm; and / or

[0185] (24) a transverse tear resistance in the range of 20N to 36N, 22N to 34N, 23N to 32N, 24N to 30N, or 25N to 28N; and / or

[0186] (25) a normalized transverse tear resistance in the range of 40 N / mm to 72 N / mm, 44 N / mm to 68 N / mm, 46 N / mm to 64 N / mm, 48 N / mm to 60 N / mm, or 50 N / mm to 56 N / mm; and / or

[0187] (26) a maximum transverse tear resistance extension in the range of 80 mm to 130 mm, 85 mm to 125 mm, 90 mm to 120 mm, 95 mm to 115 mm, or 100 mm to 110 mm; and / or

[0188] The film is characterized by one or more of the following:

[0189] (A) a haze value of less than or equal to 23%, less than or equal to 20%, less than or equal to 17%, less than or equal to 14%, or less than or equal to 10%; and / or

[0190] (B) a tensile modulus in the range of 10 MPa to 350 MPa, 15 MPa to 300 MPa, 20 MPa to 250 MPa, 25 MPa to 200 MPa, or 30 MPa to 175 MPa; and / or

[0191] (C) comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers having a tensile modulus in the range of 10 MPa to 350 MPa, 15 MPa to 300 MPa, 20 MPa to 250 MPa, 25 MPa to 200 MPa, or 30 MPa to 175 MPa; and / or

[0192] (D) comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers, having a gloss of greater than or equal to 15 GU, greater than or equal to 25 GU, greater than or equal to 35 GU, greater than or equal to 45 GU, greater than or equal to 55 GU, or greater than or equal to 65 GU; and / or

[0193] (E) comprises a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers, and having a haze of less than or equal to 65%, less than or equal to 55%, less than or equal to 45%, less than or equal to 35%, less than or equal to 25%, or less than or equal to 15%; and / or

[0194] (F) comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers having a tensile stress at break in the range of 1 MPa to 100 MPa, 2 MPa to 80 MPa, 20 MPa to 60 MPa, 25 MPa to 45 MPa, or 15 MPa to 30 MPa; and / or

[0195] (G) comprising a blend composition comprising one or more propylene-based copolymer compositions and one or more polybutylene elastomers, having an elongation at break of greater than or equal to 300%, greater than or equal to 400%, greater than or equal to 500%, greater than or equal to 600%, greater than or equal to 700%, or greater than or equal to 800%; and / or

[0196] (H) a 1% secant modulus of 30 MPa to 360 MPa, 40 MPa to 250 MPa, 50 MPa to 200 MPa, or 60 MPa to 150 MPa; and / or

[0197] (I) a 2% secant modulus of 25 MPa to 260 MPa, 30 MPa to 230 MPa, 35 MPa to 200 MPa, or 40 MPa to 150 MPa; and / or

[0198] (J) a puncture resistance of greater than or equal to 75 N, greater than or equal to 80 N, greater than or equal to 85 N, greater than or equal to 90 N, or greater than or equal to 100 N; and / or

[0199] (K) a Shore A hardness (after 15 seconds) in the range of 50 to 90, 55 to 85, 60 to 80, or 65 to 75; and / or

[0200] (L) a machine direction tear resistance of greater than or equal to 25 N, greater than or equal to 35 N, greater than or equal to 45 N, greater than or equal to 55 N, greater than or equal to 65 N, or greater than or equal to 75 N; and / or

[0201] (M) a normalized machine direction tear resistance of greater than or equal to 50 N / mm, greater than or equal to 70 N / mm, greater than or equal to 90 N / mm, greater than or equal to 110 N / mm, greater than or equal to 130 N / mm, or greater than or equal to 150 N / mm; and / or

[0202] (N) a maximum machine direction tear extension of 50 mm or more, 60 mm or more, 70 mm or more, 80 mm or more, 90 mm or more, or 100 mm or more; and / or

[0203] (O) a transverse tear resistance of greater than or equal to 25 N, greater than or equal to 35 N, greater than or equal to 45 N, greater than or equal to 55 N, greater than or equal to 65 N, or greater than or equal to 75 N; and / or

[0204] (P) a normalized transverse tear resistance of greater than or equal to 50 N / mm, greater than or equal to 70 N / mm, greater than or equal to 90 N / mm, greater than or equal to 110 N / mm, greater than or equal to 130 N / mm, or greater than or equal to 150 N / mm; and / or

[0205] (Q) Transverse tear resistance with a maximum extension of greater than or equal to 50 mm, greater than or equal to 60 mm, greater than or equal to 70 mm, greater than or equal to 80 mm, greater than or equal to 90 mm, or greater than or equal to 100 mm.

[0206] The following examples illustrate the presently disclosed compositions, films, and methods of making the same; however, those skilled in the art will recognize numerous variations within the spirit of the invention and the scope of the claims. The following examples are included to illustrate certain embodiments of the presently disclosed compositions, films, and methods of making the same. The following examples should not be construed as limiting or defining the scope of the invention.

[0207] Test Method

[0208] Listed below are test methods relevant to the properties of the above-described films and / or sheets, as shown in the following examples.

[0209] 1% secant modulus (MPa): 1% secant modulus was measured according to ASTM D638.

[0210] 2% secant modulus (MPa): 1% secant modulus was measured according to ASTM D638.

[0211] Density (g / cm 3 ): Density measurement according to ISO 1183-1.

[0212] Elongation at break (%): The elongation at break was measured according to ASTM D638.

[0213] Elongation at yield (%): The elongation at yield was measured according to ASTM D638.

[0214] Gloss (Gloss Units ("GU")): Gloss measurements were made at a 60° angle according to ASTM D-2457.

[0215] Hardness (Durometer Units): Hardness is measured by the Shore A hardness method according to ASTM D-2240.

[0216] Haze (%): Haze was measured according to ASTM 1003-13. This test depends on the film sample thickness.

[0217] Transmittance (%): Transmittance was measured according to ASTM 1003-13. This test depends on the film sample thickness.

[0218] Maximum Stretch (mm): Maximum stretch was measured according to ASTM D-1004, machine direction ("MD") and transverse direction ("TD").

[0219] Melt flow rate (g / 10 min): The melt flow rate was measured according to ASTM D 1238, ISO 1133 (MFR 230°C / 2.16kg or MFR 190°C / 2.16kg).

[0220] Nominal elongation at break (%): Nominal elongation at break was measured according to ASTM D638.

[0221] Processability: Processability is evaluated as defined above. A film sample is "processable" if the polymer tested can be successfully formed into a commercial quality cast film at a commercially acceptable rate using the equipment and conditions described in the Examples. A polymer composition has acceptable processability, or is "processable", if it can be processed into a film capable of withstanding the film performance tests herein, and if it is believed that such polymer can be continuously passed through the cast film equipment in a steady state manner under the conditions described. If the polymer composition cannot be processed into a film capable of withstanding the film performance tests herein, or if it is believed that such polymer cannot be continuously passed through the cast film equipment in a steady state manner under the conditions described, then the polymer composition does not have good processability, or is not "processable".

[0222] Puncture resistance (N): Puncture resistance was measured according to ASTM D 4833. This test depends on the film sample thickness.

[0223] Tear Resistance (N): Tear resistance is measured according to ASTM D-1004, machine direction ("MD") and transverse direction ("TD"). This test is dependent on film sample thickness.

[0224] Tensile modulus (or Young's modulus) (MPa): The tensile modulus was measured according to ASTM D-638.

[0225] Tensile Break Stress (Mpa): Tensile break stress is measured according to ASTM D-638. This test is dependent on the film sample thickness. For the measurements provided here, a thickness of 20 mils (0.51 mm) was used.

[0226] Tensile set (%): The tensile set was measured according to ISO 2285.

[0227] Example

[0228] The following examples are included to demonstrate some embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques that the inventors have found to work well in the practice of the present invention and therefore can be considered to constitute an acceptable mode of its practice. However, according to the present invention, it will be appreciated by those skilled in the art that many changes may be made to the disclosed specific embodiments without departing from the spirit and scope of the present invention and still obtaining the same or similar results.

[0229] The following examples provide compositions and films that can be used alone or in multi-layer structures as film layers, including but not limited to such layers as skin layers, soft skin layers, or PV cell encapsulants. As disclosed herein, the strength and softness of the exemplary film layers are comparable to benchmark TPO resins with higher clarity.

[0230] raw material

[0231] The raw materials used herein are shown in Table 1 below.

[0232] Table 1

[0233]

[0234] *230℃ / 2.16kg

[0235] **190℃ / 2.16kg

[0236] ***All materials purchased from LyondellBasell

[0237] In more detail, the butene-1 based copolymer plastomer ("PB") is a 1-butene ethylene copolymer having an ethylene derived unit content between 15.10 mol% and 18.00 mol%, wherein the PB has the following properties: a) a molecular weight distribution Mw / Mn lower than 3; b) a Shore A hardness (measured according to ISO 868) lower than 65; c) a tensile set at 100% deformation (ISO 2285) lower than 30%; d) no melting point can be detected on DSC during the second heating scan; e) a melting enthalpy measured after aging for 10 days at room temperature of between 4 J / g and 15 J / g. The propylene-based copolymer composition ("PBCC") is a semi-crystalline propylene copolymer composition having: (A) about 35 wt% of a propylene-based component which is a propylene / ethylene copolymer containing about 3.7 wt% of ethylene; and (B) about 65 wt% of a propylene-based component which is a terpolymer of propylene with ethylene and a C4 alpha-olefin containing about 3.3 wt% of ethylene and about 10 wt% of a C4 alpha-olefin.

[0238] TPO1 is a TPO that has a balance of strength and softness for automotive interior surface applications, but lacks the clarity required for some newer applications. Blends of a moderately modified polypropylene random copolymer ("PC") and a butene-1 based copolymer plastomer ("PB") were tried because the optical properties of both components were acceptable. However, PC / PB blends did not meet the modulus target for softness until the ratio of PB to PC was higher, at which point the blend could no longer be processed into films. Disclosed herein are blends of a propylene based copolymer composition ("PBCC") and PB. PBCC / PB blends have an improved balance of strength, softness, processability, and optical properties compared to PC / PB blends, which is believed to be due to the structural differences between PBCC and PC.

[0239] Membrane sample preparation:

[0240] Film Line 1 ("FL1"): Monolayer film samples with a thickness of 20 mils (0.51 mm) were prepared on a Killion cast film line (Killion Extruders, Inc., Cedar Grove, NJ, USA), which is a single extruder using a 0.75 inch (19 mm) screw with a pineapple-type agitator and a 6 inch (152 mm) die. The equipment has three chill rolls, but was configured to operate with two chill rolls in these experiments. Table 2 below shows the temperature settings of the equipment in these experiments:

[0241] Table 2

[0242]

[0243] Film Line 2 ("FL2"): A three-layer structure was prepared on a Killion coextrusion sheet machine (Killion Extruders, Inc., Cedar Grove, NJ, USA) capable of producing five-layer sheets, but configured as three layers, with each layer fed from one of three total extruders, each extruder having a barrel length to barrel diameter (L / D) ratio of 24:1, a barrel diameter of about 2.54 cm (1 inch) to about 3.18 cm (1.25 inches), 3 barrel heating zones, and a 10-inch flat die to produce continuous 8-inch specimens. A single-layer structure was prepared by feeding the same material through each extruder.

[0244] Examples 1-15

[0245] Examples 1-15 are sample films made on film lines 1 and 2, as shown in Table 3 below. Data are reported for specimens punched from 20 mil (0.51 mm) film and then tested according to the methods described in Tables 4-8 below. Unless otherwise noted, each example is reported as the average ("Avg.") and standard deviation ("SD") of five (5) specimens. Examples 1-6 were made from the raw materials shown in Table 1. Examples 7-9 and 11-13 are films made from blends according to the present invention. Example 15 is a multilayer film example made according to the present invention. Examples 10 and 14 are comparative examples using blends of TPO and butene-1 based polymers. TPO1 was selected as a benchmark for certain end applications to determine whether a PBCC / PB blend or multilayer film has an improved or acceptable balance of softness (tensile modulus), strength (tensile strength), and optical properties (haze, transmittance, and gloss).

[0246] Table 3

[0247] Example Sample Label Sample composition Production Line 1 TPO1-2 100% TPO1-2 FL2 2 TPO2-2 100% TPO2-2 FL2 3 TPO3-2 100% TPO3-2 FL2 4 PBCC-2 100% PBCC-2 FL2 5 PBCC-1 100% PBCC-1 FL1 6 PB-2 100% PB-2 FL2 7 70PBCC / 30PB-2 70% PBCC, 30% PB blend FL2 8 50PBCC / 50PB-2 50%PBCC, 50%PB blend FL2 9 50PBCC / 50PB-1 50%PBCC, 50%PB blend FL1 10 50TPO3 / 50PB-2 50%TPO3, 50%PB blend FL2 11 40PBCC / 60PB-1 40%PBCC, 60%PB blend FL1 12 30PBCC / 70PB-2 30%PBCC, 70%PB blend FL2 13 30PBCC / 70PB-1 30%PBCC, 70%PB blend FL1 14 30TPO3 / 70PB-2 30% TPO3, 70% PB blend FL2 15 PBCC / PB-3L-2 25%PBCC, 50%PB, 25%PBCC - 3 layers FL2

[0248] Optical performance

[0249] Table 4 below shows the test results of the optical properties of gloss and haze of Examples 1-15.

[0250] Examples 1-3 show that the gloss of the films from the tested TPOs ranges from 17.2 GU to 44.4 GU, and the haze ranges from 26.9% to 59.7%. Examples 4 and 5 show that the gloss of the films from the tested propylene-based copolymers ranges from 72.9 GU to less than 100 GU, and the haze ranges from 10.6% to 23.3%. Example 6 shows that the gloss of the films from the tested butene-1-based copolymers is 8.8 GU, and the haze is 86.8%.

[0251] Inventive Examples 7-9 comprised 50% to 70% blends of the propylene-based copolymer composition with a butene-1 based copolymer, and had gloss ranging from 14.2 GU to 73.9 GU and haze ranging from 12.52% to 52.4%. Comparative Example 10 comprised a blend of similar amounts of TPO with a butene-1 based copolymer, and had a gloss of 8.8 GU and a haze of 86.8%. Examples 7-11 demonstrate that the blends of the propylene-based copolymer composition with a butene-1 based copolymer have improved gloss and haze compared to similar blends of TPO with a butene-1 based copolymer.

[0252] Inventive Examples 11-13 comprised 30% to 40% blends of the propylene-based copolymer composition with a butene-1-based copolymer, and had gloss ranging from 16.1 GU to 85.7 GU and haze ranging from 6.99% to 63.4%. Comparative Example 14 comprised a blend of similar amounts of TPO with a butene-1-based copolymer, and had a gloss of 15.5 GU and a haze of 69.7%. Examples 11-14 demonstrate that the blends of the propylene-based copolymer composition with a butene-1-based copolymer have improved gloss and haze compared to similar blends of TPO with a butene-1-based copolymer.

[0253] Inventive Example 15 comprises an A / B / A three-layer film, wherein each A layer is a propylene-based copolymer composition, comprising 25% of the film thickness, and a B core layer is a butene-1-based copolymer, comprising 50% of the film thickness. Thus, Example 15 is a film comprising 50% propylene-based copolymer composition and 50% butene-1-based copolymer. As with the blends of the propylene-based copolymer composition and the butene-1-based copolymer, Example 15 demonstrates that the combination of layers of the propylene-based copolymer composition and the butene-1-based copolymer produces a film having better gloss and haze than Examples 10 and 14 using a similar amount of TPO blended with a butene-1-based copolymer.

[0254] Additional effects were observed in the blend population of PBCC and PB, as films processed on FL1 exhibited better optical properties compared to films processed on FL2. Examples 8, 9, and 15 all contained 50 wt% PBCC. However, inventive blend Example 9 and inventive multilayer Example 15 exhibited gloss values ​​of 73.9 GU and 52.2 GU, respectively, and haze values ​​of 12.52% and 14.35%, while Example 8 had a gloss of 14.2 GU and a haze of 52.4%. Example 11 was processed on FL1 and contained 40 wt% PBCC, with a gloss of 85.7 GU and a haze of 6.99%. Example 13 was processed on FL1 and contained 30 wt% PBCC, with a gloss of 57.9 GU and a haze of 16.97%. Example 12 was processed on FL2 and had a gloss of 16.1 GU and a haze of 63.4%. This shows that the gloss of processing a film having a blend or layer of PBCC and PB as disclosed herein can be increased threefold when processing a film on FL1 compared to a film on FL2, and the haze is reduced by one-third when processing a film on FL1 compared to a film on FL2. Examples 8, 9, and 15 all contain 50 wt% PBCC.

[0255] The blends of Examples 7-9, 11-13 and 15 show improved gloss and haze compared to PBCC alone. Examples 9, 11 and 14 were produced on FL1 and Examples 7, 8, 12, 13 and 15 were produced on FL2. It should be noted that FL2 is not designed to produce films with specific optical properties. Without wishing to be bound by any particular theory, it is believed that based on the observation that the surface appearance of these blends is inconsistent, the optical properties are somewhat reduced when the blends containing PB come into contact with the cooling rolls in FL2 configured for these experiments. However, the optical properties of Examples 7-9, 11 and 13 show favorable and reliable trends. Since the outer layer contains only PBCC, Example 15 is also believed to show improved optical properties even though it was produced on FL2.

[0256] The transmittance of Examples 6-8, 12, and 13 was measured using a film thickness of 20 mils (0.51 mm). In solar applications, transmission results equal to or greater than 90% are meaningful. As shown in Table 4, Examples 6-8, 12, and 13 all have transmission levels of 91% or higher. This indicates that the films described presently will allow light to pass through the solar cell component layers to the components below, such as PV electronic components. For automotive applications, transmittance is not as important as haze, which affects "clarity" or readability. However, these transmission levels are also acceptable for automotive applications.

[0257] Table 4

[0258]

[0259] Tensile properties

[0260] Table 5 below shows the test results related to tensile properties, specifically tensile stress at break and elongation at break. Examples 1-6 show the tensile properties of the raw materials. Examples 7-9, 11-13 and 15 show examples prepared according to the present invention. Examples 10 and 14 are comparative examples. Testing was performed according to ASTM D-638. The crosshead speed was 20 inches / minute (8.5 mm / second). The tensile strength of Examples 6-10 and 12-14 is reported as the stress at maximum elongation, and all examples reached a maximum elongation of >800% without breaking.

[0261] Based on the weighted average of the composition, the predicted values ​​of the tensile stress at break for inventive examples 7-9, 11-13 and 15 are 25.8 MPa, 21.7 MPa, 21.7 MPa, 19.62 MPa, 17.58 MPa, 17.58 MPa and 18.60 MPa, respectively. For examples 7-9, 11-13 and 15, the measured tensile stress at break compared to the predicted tensile stress at break (expressed as a percentage) are 113%, 111%, 100%, 94%, 100%, 108% and 107%, respectively, with an average of these values ​​of 105%. Based on the weighted average of the composition, the predicted values ​​of the tensile stress at break for comparative examples 10 and 14 are 18.6 MPa and 15.74 MPa, respectively. For examples 10 and 14, the measured tensile stress at break compared to the predicted tensile stress at break (expressed as a percentage) are 108% and 103%, respectively, with an average of these values ​​of 105%. It is believed that this indicates that the tensile stress at break of the film of the blend or layer of PBCC or TPO with PB is a weighted average of the tensile stress at break of the individual components. The tensile stress at break of PBCC is equal to or higher than the TPO tested. Therefore, it is believed that the PBCC / PB combination has an equal or higher tensile stress at break than the TPO / PB combination with the same PB content.

[0262] Although the values ​​of elongation at break and nominal elongation at break were recorded, none of the specimens in Examples 8-14 actually broke before the test apparatus was fully extended. Only two specimens broke in Example 7. Example 15 reported an elongation at break value of 750 MPa and a nominal elongation at break value of 590 MPa. These parameters are an indicator of the polymer's resistance to shape change without forming cracks. Since the elongation at break and nominal elongation at break for all Examples 7-15 exceeded 500%, it is believed that the performance of these films in the intended application does not differ on this basis, i.e., no meaningful performance loss in these parameters occurs due to the replacement of TPO with PBCC in the film.

[0263] It is believed that for the intended applications between Inventive Examples 7-9, 11-13, and 15 and Comparative Examples 10 and 14, the reported values ​​of tensile yield and elongation at yield do not show meaningful differences in these parameters.

[0264] Table 5

[0265]

[0266] 1. One specimen did not break.

[0267] 2. None of the specimens broke and achieved full extension of the frame.

[0268] 3. None of the specimens yielded.

[0269] 4. Two specimens did not break.

[0270] Table 6 below shows the results of further testing related to tensile properties of 1% secant modulus, 2% secant modulus, and tensile modulus (Young's modulus). Examples 1-6 show the tensile properties of the raw materials. Examples 7-9, 11-13, and 15 show examples prepared according to the present invention. Examples 10 and 14 are comparative examples. Testing was performed according to ASTM D-638. The crosshead speed was 0.5 inches per minute (0.21 mm per second). All specimens were Type IV.

[0271] For the intended applications between Inventive Examples 7-9, 11-13, and 15 and Comparative Examples 10 and 14, it is believed that the reported values ​​for 1% secant modulus, 2% secant modulus, and tensile modulus do not show meaningful differences in these parameters.

[0272] Table 6

[0273]

[0274] 1. Only four specimens were averaged. One had equipment failure.

[0275] 2. Only three specimens were averaged. Two had equipment failures.

[0276] 3. Use 0.05 (as little as one-tenth) pound preload.

[0277] 4. Use normal 0.5 lb preload.

[0278] Puncture resistance and hardness

[0279] Table 7 below shows the test results for puncture resistance and hardness of Examples 1, 6-8, 12, and 14. Puncture resistance testing was performed according to ASTM D-4833. Shore A hardness testing was performed according to ASTM D-2240. However, because individual specimens did not meet the minimum thickness requirement, multiple specimens were stacked for hardness testing. These samples were all prepared on FL2.

[0280] Example 1 shows the puncture resistance and hardness of benchmark TPO 1-2. Example 6 shows the puncture resistance and hardness of PB. Inventive Examples 7, 8 and 12 show puncture resistance of 116.1 N, 102.3 N and 90.9 N respectively, which are better than the 70.47 N measured for Comparative Example 14. For the intended applications between Inventive Examples 7, 8 and 12 and Comparative Example 14, it is believed that the reported Shore A hardness values ​​do not show a meaningful difference in this parameter.

[0281] Table 7

[0282]

[0283] Puncture resistance and hardness

[0284] Table 8 below shows the test results for machine direction and cross direction tear resistance of Examples 1, 6-8, 12 and 14. Puncture resistance testing was performed according to ASTM D-1004. Tear resistance testing was performed according to ASTM D-1004. These samples were prepared on FL2. The film thickness of the samples is shown in the column titled "T".

[0285] Example 1 shows the tear resistance of benchmark TPO1-2. Example 6 shows the tear resistance of PB-2. Inventive Examples 7, 8 and 12 show MD tear resistance of 102.3N, 72.1N and 48.0N, respectively, which are better than the 46.6N measured in Comparative Example 14. Inventive Examples 7, 8 and 12 show TD tear resistance of 101.0N, 71.3N and 45.8N, respectively, which are better than the 45.2N measured in Comparative Example 14.

[0286] Table 8

[0287]

[0288] Although the present invention and its advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made here without departing from the spirit and scope of the present invention as defined by the appended claims. The scope of various features and attributes disclosed herein is listed as a narrowed scope in sequence. However, it should be understood that for the same features or attributes, any lower endpoint of any scope can be paired with any upper endpoint, and such pairing is also intended to be disclosed herein. In addition, the scope of the present application is not intended to be limited to the specific embodiments of the process, machine, film structure, composition, device, method and / or step described in the specification. As will be easily understood by those of ordinary skill in the art from the disclosure of the present invention, according to the present invention, the process, machine, film structure, composition, device, method and / or step of the layer that currently exists or will be developed later to perform the same function as the corresponding embodiment described herein or to achieve substantially the same result can be used. Therefore, the appended claims are intended to include such processes, machines, film structures, composition, means, methods and / or steps of layers within their scope.

Claims

1. A composition comprising: a. a propylene-based copolymer composition; and b. Polybutylene elastomer; in: i. blending the propylene-based copolymer composition and the polybutylene elastomer under melt conditions to form the composition, and ii. The composition has a haze value of less than or equal to 23%, and a tensile modulus in the range of 10 MPa to 350 MPa.

2. The composition according to claim 1, wherein The propylene-based copolymer composition is a blend of random copolymers of propylene and one or more α-olefins.

3. The composition according to claim 1, wherein The propylene-based copolymer composition has a melt flow rate (230° C. / 2.16 kg) in the range of 0.9 g / 10 min to 7.5 g / 10 min.

4. The composition according to claim 1, wherein The density of the propylene-based copolymer composition is 0.88 g / cm 3 Up to 0.92g / cm 3 within the range.

5. The composition according to claim 1, wherein The propylene-based copolymer composition has a tensile modulus in the range of 100 MPa to 1000 MPa.

6. The composition according to claim 1, wherein The propylene-based copolymer composition is a blend of at least two random copolymers, wherein the random copolymer is a random copolymer of propylene and one or more α-olefins.

7. The composition according to claim 6, wherein The random copolymers of propylene and one or more alpha-olefins are produced in a polymerization process using a spherical Ziegler-Natta catalyst.

8. The composition according to claim 7, wherein The polymerization process comprises two or more gas phase reactors operated in series.

9. The composition according to claim 1, wherein The polybutene elastomer has a melt flow rate (190C / 2.16kg) in the range of 0.5 g / 10 min to 4 g / 10 min.

10. The composition according to claim 1, wherein The density of the polybutene elastomer is 0.870 g / cm 3 Up to 0.915g / cm 3 within the range.

11. The composition according to claim 1, wherein The tensile modulus of the polybutene elastomer is in the range of 1 MPa to 100 MPa.

12. The composition according to claim 1, wherein The tensile elongation at break of the polybutene elastomer is greater than or equal to 300%.

13. The composition according to claim 1, wherein The polybutene elastomer is polymerized in a process comprising a metallocene catalyst, a Ziegler-Natta catalyst, or a combination thereof.

14. The composition according to claim 1, wherein The propylene-based copolymer composition is present in the composition in an amount ranging from 20 wt% to 80 wt%, and the polybutylene elastomer is present in the composition in an amount ranging from 20 wt% to 80 wt%, wherein all weight percentages are based on the combined weight of the propylene-based copolymer composition and the polybutylene elastomer.

15. A film comprising the composition according to claim 1.

16. The film according to claim 15, wherein The membrane comprises: a. two outer layers comprising the propylene-based copolymer composition; and b. A core layer comprising the polybutylene elastomer, wherein the core layer is disposed between the two outer layers.

17. The film according to claim 16, wherein The thickness of the core layer is in the range of 50% to 85% of the total thickness of the core layer and the two outer layers.

18. A process for making a film, the process comprising: a. blending the propylene-based copolymer composition and the polybutylene elastomer under melt conditions to form a blended melt composition; and b. extruding the blended melt composition to form the film; The haze value of the film is less than or equal to 30%, and the tensile modulus is in the range of 10 MPa to 350 MPa.

19. The process of claim 18, wherein: The propylene-based copolymer composition is a blend of random copolymers of propylene and one or more α-olefins.

20. The process of claim 18, wherein: The polybutene elastomer has a melt flow rate (190C / 2.16kg) in the range of 0.5 g / 10 min to 4 g / 10 min.